Efficacy and Safety of Tenofovir-Containing Antiretroviral Therapy in Women who Acquired HIV while Enrolled in Tenofovir Gel Prophylaxis Trials. Issue 4 (May 2017) - Naicker, Nivashnee; Naidoo, Anushka; Werner, Lise; Garrett, Nigel; Majola, Nelisile; Asari, Villeshni; Baxter, Cheryl; Grobler, Anneke; Karim, Quarraisha Abdool; Karim, Salim S Abdool
Background: We assessed whether women who acquired HIV during tenofovir gel prophylaxis trials can be safely and effectively treated with tenofovir-containing anti-retroviral therapy (ART). Methods: Between May 2011 and October 2014, HIV seroconvertors from two tenofovir gel trials were recruited when eligible for ART (CD4 + T-cell count <350 cells/ml, pregnancy or AIDS-defining illness). Women were randomized to tenofovir-containing (tenofovir + lamivudine/emtricitabine + efavirenz) or tenofovir-sparing (zidovudine + lamivudine/emtricitabine + efavirenz) antiretroviral treatment regimens. The proportion with virological suppression, adverse events and drug switches were compared. Results: Fifty-nine women were enrolled and followed-up for median 18 months (IQR 6–24). Twenty-nine women (7 tenofovir gel exposed, 22 tenofovir gel unexposed) were randomized to a tenofovir-containing and 30 (9 tenofovir gel exposed, 21 tenofovir gel unexposed) to a tenofovir-sparing regimen. Median baseline CD4 + T-cell count and viral load (VL) were 345 cells/ml (IQR 280–423) and 4.5 log copies/ml (sd 0.79), and did not differ by ART assignment. Overall VL suppression rates were 88.0% and 78.3% at 6 months ( P =0.454) and 85.7% and 79.0% at 12 months ( P =0.689) in women on the tenofovir-containing and tenofovir-sparing regimens, respectively. Toxicity-related drug switches were more frequent in women on the tenofovir-sparing than tenofovir-containing regimen (36.7% versus 0.0%, P <0.001). Conclusions: Preliminary data show that tenofovir-containing ART was effective and more tolerable in HIV seroconvertors from tenofovir gel prophylaxis trials and may be considered for use in women with prior tenofovir gel exposure. Clinical trials.gov NCT01387022.